Market Discipline and Incentive Problems in Conglomerate Firms with Applications to Banking - Boot, Arnoud W.A.; Schmeits, Anjolein (Journal of Financial Intermediation, 2000)
This paper analyzes the optimality of conglomeration. We show that the potential benefits of conglomeration depend critically on the effectiveness of market discipline for stand-alone activities. Effective market discipline reduces the benefits of conglomeration. With ineffective market discipline of stand-alone activities, conglomeration would further undermine market discipline, but may nevertheless be beneficial. In particular, when rents are not too high, the diversification benefits of conglomeration dominate the negative incentive effects. A more competitive environment therefore induces conglomeration. We also show that introducing internal cost-of-capital allocation schemes creates internal market discipline that complements the weak external market discipline of a conglomerate. Our analysis sheds light on the Barings debacle and other recent developments in the banking sector. Journal of Economic Literature Classification Numbers: G20, G21, G34.